Rancang Bangun Alat Penyiraman Dan Pembasmi Hama Otomatis Pada Tanaman Bayam Dengan Monitoring Berbasis Website - Thooriq, Muhammad Ath; Sujatmika , Arif Rahman; Umami , Izzatul (Jurnal Sains dan Teknologi (JSIT), 2023)
Spinach is one type of plant whose leaves can be consumed, because it contains iron which is useful for the body, people often use it for their daily vegetable needs. Spinach plants cannot grow properly if the water content in the soil does not meet the needs of the plants. In addition, spinach plants are susceptible to pest attacks that can damage the leaves. From these two problems, we need a system of automatic watering and pest control devices that can monitor plants. To make it easier to plant spinach, a monitoring system is needed using a website, because its use which can be accessed anywhere for 24 hours can make it easier to monitor the condition of spinach plants. The website will display soil moisture and PIR sensor data readings sent via the NodeMCU ESP8266 microcontroller to a database in the form of soil percentage, soil status, and plant conditions.